YouTube and English Learning: Transformative Impact on Self-Regulated Learning Competencies - Rusdi, Lathifatuddini; Asma, Asma; Husna, Anna; Karimipour, Marjan (Idarah (Jurnal Pendidikan dan Kependidikan), 2023)
The awareness of learning English has risen not only on students but also general community. However, expecting to master English merely relies on classroom learning or formal setting are considered not sufficient. Therefore, more English learners both students and public figured out how to study by themselves. The emergence of YouTube has changed the way people learn English. The various kinds of videos and their flexibility of access raised their awareness to learn English individually. It is a qualitative study. The data were analysed based on (Miles et al., 2014) theory. The researchers interviewed three participants to collect the data. They were selected based on the criteria managed by the researcher. This study used three competencies of self-regulated learning (SRL): cognitive, motivation and metacognitive. This study found that YouTube positively impacted SRL. The participants proved that YouTube helped them to understand English better, made their learning fun and enabled them to reflect their English competence.